Development of a compact pulsed time-of-flight LiDAR platform for underwater measurements - Werner, Christoph S.; Gangelhoff, Jannis; Frey, Simon; Steiger, Daniel; Reiterer, Alexander (The International Hydrographic Review, 2025)
The mapping and inspection of underwater topography and infrastructure require precise and robust instrumentation which cannot be completely fulfilled by sonar or camera-based systems. At Fraunhofer IPM we have therefore built a versatile platform that implements all necessary building blocks for various laser scanner configurations targeted at subsea applications. Based on this platform, we present two scanner prototypes: One compact and lightweight multi-wavelength airborne laser scanner for deployment with unmanned aerial vehicles. It is intended for easy and fast shallow water bathymetric and topographic mapping. The second scanner is embedded in a pressure resistant housing and designed for submerged deployment on stationary or moving platforms to facilitate numerous inspection tasks. Initial tests of the scanners have been performed in an excavation pond and on a dedicated underwater measurement range. The resulting point clouds indicate promising performance in terms of resolution, accuracy, and speed. Further work will focus on extensive field tests and software optimization for increased usability.